Neurological outcome at 24 months corrected age of prematurely born infants after preterm premature rupture of membranes (PPROM) of at least 7 days: a two-center experience in Germany. (17th April 2020) - Müller, Hanna; Storbeck, Tobias; Katzer, David; Bruns, Nora; Wössner-Stegmann, Gaby; Ai, Maria; Köninger, Angela; Müller, Andreas; Felderhoff-Müser, Ursula; Bagci, Soyhan
Abstract: Objective: Preterm premature rupture of membranes (PPROM) is a risk factor for chorioamnionitis (CA) and injury to the fetal brain. However, prolongation of gestation prevents morbidity and decreases complications of prematurity. The current investigation is to define risk factors for the adverse neurological outcome from the influence of PPROM of at least 7 days. Methods: A case–control study included three groups of preterm infants born at the University Hospitals Bonn and Essen, Germany. The first group consisted of infants with PPROM of at least 7 days and no chorioamnionitis (CA) (PPROM group), the second included preterm infants with CA (CA group), and the third group consisted of infants without PPROM and CA (control group). The outcome was assessed using Bayley Scales of Infant Development at a corrected age of 24 months. Each group consisted of 20 corresponding infants with an identical birth weight and gestational age at birth. Results: There was no significant difference between the mental development index (MDI) and psychomotor development index (PDI) scores (mean ± SD): the MDI score was 101 ± 14 in the PPROM group, 98 ± 12 in the CA group and 96 ± 17 in the control group; the PDI score 96 ± 10, 89 ± 16, and 90 ± 17, respectively. Multiple regression analysis revealed no significant influence of PPROM and CA on neurological outcome. Conclusions: PPROM of at least 7 days has no influence on neurodevelopmental outcome at a corrected age of 24 months when birth is initiated in the case of beginning CA.